Performance evaluation of reformulated query for information retrieval using real estate ontology. (8th September 2021) - Rastogi, Namrata; Verma, Parul; Kumar, Pankaj
The data over the internet is growing at an unprecedented rate daily. Hence efficient information retrieval has always been at stake. The scenario becomes more tedious in an e-government sector like real estate where fetching of legal documentation used for buying and selling of land property is unknown to novice users. The uncommon legal terminology also dilutes the keyword-based retrieval system. The proposed system thus insists on creating and further utilising ontology in this semantic web era. The performance of information retrieval is measured by calculating various parameters like mean average precision, precision@k, and normalised discounted cumulative gain for general user query first and then comparing it with the reformulated query after applying the real estate ontology. The experimental results are further statistically checked to depict an improvement in all the parameters thereby indicating that an initial user query, after ontological reformulation improves the efficiency of the information retrieval process.